Comparative study of glucometer and laboratory glucose oxidase method for the estimation of blood glucose levels in neonates - Dr. Farah Naaz; Dr. R.K.Gulati (Pediatric Review: International Journal of Pediatric Research, 2019)
Introduction: Hypoglycemia is one of the most common metabolic problems encountered in neonates. The glucose oxidase method used in the laboratory for determining the blood glucose concentration is precise and specific for glucose. The glucometers are often used for blood glucose estimation in NICU. Objectives: This is a prospective study done to determine the efficacy of glucometer in estimation of blood glucose levels in neonates in comparison with the laboratory values. Methods: 170 neonates admitted in NICU in Jay Kay Lon Hospital, Kota associated with Government Medical College Kota with varied symptomatology were enrolled in this study. Blood glucose estimation was done by glucometer and laboratory method using the same venous sample at the time of admission. Statistical analysis was done by using Pearson correlation. Hypoglycemia was defined as blood glucose level <45mg%. Laboratory value was taken as gold standard. Results: Hypoglycemia was common in neonates with risk factors like prematurity, meconium aspiration, septicemia, birth asphyxia etc. In our study Glucometer had a specificity of 98.20%, sensitivity of 64.48 %, positive predictive value of 95%, negative predictive value of 83.84% and accuracy of 86.47%. There was good correlation and no significant difference between two methods in the range between 45 mg/dl and 145 mg/dl but not at very high or very low glucose concentrations Conclusion: The ‘Point of care “device - glucometer as a sole measuring device to screen neonatal hypoglycemia is not satisfactory and confirmation with the laboratory measurements of plasma glucose is still of up most importance.